10 Wochen alter Säugling mit Sepsisverdacht und SARS-CoV-2-Nachweis in Liquor und Rachen - Färber, Katharina (Monatsschr Kinderheilkd, 2020)
A young male infant was referred to the emergency department with apparent acute sepsis. The laboratory results were compatible with a viral infection except for a slightly elevated procalcitonin level. Due to the clinical severity intravenous antibiotic treatment was started immediately. Cerebrospinal fluid and urine testing initially showed no infection focus but then SARS-CoV‑2 was detected in the lower pharynx and cerebrospinal fluid. The clinical condition of the infant rapidly improved but whether this was due to symptomatic or antibiotic treatment remained unknown. There is still a considerable lack of experience regarding diagnostics and treatment of pediatric SARS-CoV-2 infections.